2018
DOI: 10.1002/oby.22337
|View full text |Cite
|
Sign up to set email alerts
|

Weight Trends in Veterans With and Without Diabetes, 2000 to 2014

Abstract: Objective: To assess weight trends and diabetes prevalence among US veterans. Methods: We used information from the Veterans Affairs (VA) Informatics and Computing Infrastructure (VINCI) Corporate Data Warehouse (CDW) to construct datasets that included demographic data, diabetes status, and weight observations for males and females. Secular and longitudinal trends in mean weight were analyzed. Results: 4,527,865 patients born from 1915-1984 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Veterans are not only found to suffer from obesity at higher levels when compared to the average U.S. population [ 6 , 7 ], but also suffer from a significantly higher level of associated co-morbidities including coronary heart disease-CHD or angina; stroke; skin cancer; other cancers; chronic obstructive pulmonary disease (COPD), emphysema, or chronic bronchitis; arthritis, rheumatoid arthritis, gout, lupus, or fibromyalgia; depressive disorders; and diabetes [ 1 , 8 , 9 , 10 ]. Particularly concerning is the interaction of depression, diabetes, and obesity and their associated health outcomes [ 6 , 11 , 12 ]. Coupled with the growing ‘obesity epidemic’ impacting the U.S., it is important to identify geographic locations where Veteran populations reside so as to better resource health intervention programs aiming to meet the health needs of Veterans [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Veterans are not only found to suffer from obesity at higher levels when compared to the average U.S. population [ 6 , 7 ], but also suffer from a significantly higher level of associated co-morbidities including coronary heart disease-CHD or angina; stroke; skin cancer; other cancers; chronic obstructive pulmonary disease (COPD), emphysema, or chronic bronchitis; arthritis, rheumatoid arthritis, gout, lupus, or fibromyalgia; depressive disorders; and diabetes [ 1 , 8 , 9 , 10 ]. Particularly concerning is the interaction of depression, diabetes, and obesity and their associated health outcomes [ 6 , 11 , 12 ]. Coupled with the growing ‘obesity epidemic’ impacting the U.S., it is important to identify geographic locations where Veteran populations reside so as to better resource health intervention programs aiming to meet the health needs of Veterans [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Veterans are at a higher risk for diabetes with potentially poorer outcomes. The prevalence of diabetes among veterans enrolled in the Veterans Affairs (VA) Veterans Health Administration is 3 times higher than that of the general US population, 1,2 placing them at higher risk for chronic microvascular and macrovascular complications. 3 Several factors have been identified for this disproportionate risk primarily related to veterans' higher rate of overweight and obesity.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Weight gain throughout the life cycle is also a considerable problem and data show that mean body weight among women veterans increased from 2000 to 2014. 3 …”
Section: Introductionmentioning
confidence: 99%
“…2 Weight gain throughout the life cycle is also a considerable problem and data show that mean body weight among women veterans increased from 2000 to 2014. 3 Although the military places an emphasis on fitness and maintaining a healthy weight, research demonstrates veterans have a propensity to be overweight or of obese status after military discharge due to significant changes in eating habits, physical activity, and psychological comorbidity. 4 A study of veteran's weight trajectory demonstrated women who left the military during the time of followup gained an average of 6.3 kg within a 6-year period compared with 4 kg in women who continued their military service.…”
Section: Introductionmentioning
confidence: 99%